Exploring the Impact of Rehabilitation and Custody Orientations on Workplace Experiences of Juvenile Probation and Detention Officers - Rhineberger, Gayle (Criminal justice policy review, 2024)
Prior research has suggested that juvenile justice staff’s support for rehabilitation is important for the success of their juvenile clients. The purpose of this article was to assess how rehabilitation and punishment orientations impacted burnout, secondary trauma, job stress, and job satisfaction among juvenile probation and detention officers. Results indicated that having more of a rehabilitation orientation did not demonstrate direct effects on the workplace outcomes included in this study. However, staff who indicated more of a punishment orientation were less likely to report emotional exhaustion and personal accomplishment, as well as less job stress, but were more likely to report feelings of depersonalization.